KINERJA GURU PADA HOMESCHOOLING KAK SETO DI KECAMATAN SAIL KOTA PEKANBARU - Sandro Pandapotan P; Wilson '; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The formulation of the problem in this research is to find out whether Teacher Performance At Homeschooling Kak Seto In Sail Sub-District Pekanbaru Is Good? The purpose of this study is to determine the performance of teachers at homeschooling kak seto in the sail district of Pekanbaru city. Benefits of this research as input ingredients for researchers in adding insight, knowledge and think critically and analysis. The population in this research are teachers in Homeschooling Kak Seto In Kecamatan Sail Pekanbaru City as many as 30 people and sample in this research is 20 people elsewhere used as sample of trial conducted in PKBM Bina Kreasi in Jalan Harapan Raya Pekanbaru City. Sampling in this research use Descriptive research with quantitative approach. The instrument used in this study is a questionnaire containing 48 statement items, Teacher Performance at Homeschooling Kak Seto In Sail Sub-district Pekanbaru City, with indicators 1) ability to plan lesson, 2) ability to implement learning, 3) ability to carry out assessment of learning outcomes. Alternative answers every item statement has a category strongly agreed to be given 4 (four), agree to be given a score of 3 (three), less agree given a score of 2 (two) and not agree to score 1 (one). From the results of research in the know that the Performance Teachers At Homeschooling Kak Seto In Sail District Pekanbaru City is referred to in this study are teachers who work on Homeschooling into the category very well. This is evidenced from the exposure of data recapitulation, namely: 1) the ability to prepare lesson plans, 76% of respondents stated strongly agree (SS) and seuju (S). 2) ability to implement learning 80% of respondents who stated strongly agree (SS) and agree (S). 3) ability to carry out assessment of learning outcomes 77% of respondents who stated strongly agree (SS) and agree (S). Meaning Performance Teachers At Homeschooling Kak Seto In Sail Sub-district Pekanbaru is in very good category because it shows that the three components of teacher performance in the ability to arrange the learning plan, the ability to implement the learning, the ability to carry out the assessment of learning outcomes, good performance.Keywords: Performance of teachers, Homeschooling